Transformational Leadership: How Intrinsic Motivation and Innovation at Workplace - Satriawan, Bambang; Dewi, Nolla Puspita; Yanti, Sri; Yuliansyah, Yuliansyah (Universitas Bangka Belitung, 2025)
This study aims to examine the relationship between transformational leadership and the improvement of employees' innovative performance in the service division of Regional Apparatus Organizations in Karimun Regency, Riau Islands Province. This quantitative research uses a non-probability random sampling technique. There are 100 respondens participated in this research, with primary data collected through questionnaires. Data analysis includes descriptive statistics, data quality tests, outer and inner model tests, and hypothesis testing using. The results show that transformational leadership has a significant positive effect on innovative performance. Intrinsic motivation also positively and significantly affects innovative performance. Furthermore, transformational leadership significantly influences intrinsic motivation and indirectly enhances innovative performance through intrinsic motivation. This study highlights the importance of transformational leadership in fostering employee motivation and innovation within local government organizations.